2021
DOI: 10.23887/paud.v9i3.41385
|View full text |Cite
|
Sign up to set email alerts
|

E-Modul Strategi Pembelajaran Anak Usia Dini Sebagai Sumber Belajar Digital

Abstract: Era digital berdampak pada semua aspek kehidupan termasuk dalam pendidikan dan pembelajaran. Pembelajaran berubah dari pola tatap muka menuju ke arah dalam jaringan. Kemudahan dan mobilitas pembelajaran untuk mahasiswa S1 PGPAUD belum didukung oleh sumber belajar yang fleksibel, mudah diakses dan adaptif serta terprogram, sehingga mereka masih tergantung pada kehadiran dosen melalui web meeting dan atau tatap muka. Untuk memecahkan permasalahan tersebut, diperlukan sumber dan program pembelajaran yang efektif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
0
15
0
4
Order By: Relevance
“…The magnitude of the benefits that e-modules have for learning activities raises opportunities and assumptions for the design and development of e-modules to be used routinely for learning in vocational schools. Electronic modules are learning tools or means which contains materials, methods, limitations and methods of evaluating that are designed in a systematic and attractive manner to achieve the expected competencies according to their level of complexity electronically (Imansari & Sunaryantiningsih, 2017;Sutama et al, 2021). If applied to concierge materials, experiential learning-based electronic modules can be used as alternative learning resources that make it easier for students to learn and get rid of learning conditions that tend to be boring.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the benefits that e-modules have for learning activities raises opportunities and assumptions for the design and development of e-modules to be used routinely for learning in vocational schools. Electronic modules are learning tools or means which contains materials, methods, limitations and methods of evaluating that are designed in a systematic and attractive manner to achieve the expected competencies according to their level of complexity electronically (Imansari & Sunaryantiningsih, 2017;Sutama et al, 2021). If applied to concierge materials, experiential learning-based electronic modules can be used as alternative learning resources that make it easier for students to learn and get rid of learning conditions that tend to be boring.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the data helps students visualize the photo more naturally.Studies have shown that hyper-content modules for early childhood education benefit improving HOTS abilities (Sutama, Astuti, Pramono, et al, 2021), teaching linguistic aspects (Ningsih & Mahyuddin, 2021), increasing creativity (Fitriani et al, 2022), improving computational thinking (Muthmainnah Harahap, 2022). The modules can be a digital learning resource in early childhood education study programs (Sutama, Astuti, & Anisa, 2021). There is limited evidence in the literature regarding students' opinions on the importance of digital skills in learning hyper-content modules for them.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Pada setiap lembanga PAUD peneliti mengambil masing -masing 2 guru sehingga jumlah sampel yang digunakan yaitu sebanyak 10 responden (guru). Berdasarkan hasil penilaian guru terhadap produk rancangan pembelajaran berbasis aplikasi Tahu Terguri dalam uji coba lapangan skala besar yaitu 2 orang responden memperoleh jumlah skor 37 dengan normatif katagorisasi baik, 5 orang responden mendapat jumlah skor 38 dengan normatif katagorisasi baik, dan 3 orang responden medapatkan jumlah skor 39 dengan normatif katagorisasi baik dari hasil tersebut dapat dianalisis rancangan pembelajaran berbasis aplikasi tahu terguri bagi guru PAUD, berada pada persentase 100% dengan katagori Baik, atau aplikasi Tahu Terguri layak digunakan dalam merancang perangkat pembelajaran anak usia dini berbasis digital, hal ini menjadi tantangan bagi guru atau lembaga pendidikan agar dalam pembelajaran menekankan pada pengalaman belajar yang mengarah pada kompetensi keterampilan inovatif dan kreatif, kolaboratif dan membangun networking serta berkomunikasi secara efektif (Sutama et al, 2021). Oleh karena itu diperlukan literasi digital.…”
Section: Validasi Ahli Setelah Uji Coba Skala Kecilunclassified